Enhancing the Cultural Heritage through Adaptive Reuse. A Multicriteria Approach to Evaluate the Castello Visconteo in Cusago (Italy) - Dell’Ovo, Marta; Dell’Anna, Federico; Simonelli, Raffaella; Sdino, Leopoldo (Sustainability, 2021)
Cultural heritage can play a strategic role in developing a sustainable built environment, contributing to the improvement of the economic, social, and environmental productivity of a city. Human activities are constantly affecting the quality of the environment and altering the ecosystems, which produce negative consequences also on human wellbeing. Within this context, it has been much discussed how cities and the built environment can counteract this process by supporting more sustainable development. Adaptive reuse is defined as “a process that changes a disused or ineffective item into a new item that can be used for a different purpose”, which strongly triggers the sustainable development of cities. It can be recognized as a promoter of economic growth, social wellbeing, and environmental preservation, given its capability of both preserving past values and creating new ones. The adaptive reuse matches the main points of the circular economy, seen as the sustainable economy, which is aimed at the reduction of natural resource extraction and environmental impact by extending the useful life of materials and promoting recovery, reuse, and regeneration processes. Given these premises, the current contribution aimed to evaluate alternative scenarios for reuse in Castello Visconteo in Cusago, located in the Lombardy region (Italy), and understanding how adaptive reuse could contribute to generating new values within a circular economy perspective. In detail, four alternative scenarios were proposed to face the new needs born during the COVID-19 pandemic period. Since both intangible and tangible values must be considered, a multicriteria decision analysis (MCDA) has been applied by combining economic and qualitative indicators to define the most suitable function for its adaptive reuse. In detail, the Novel Approach to Imprecise Assessment and Decision Environments (NAIADE) was used to identify the best alternative solution based on the opinions of conflicting stakeholders. The innovativeness of the contribution is given by the combination of different methodologies, the preservation of the memory and the generation of new values, and the consideration of adaptive reuse as a strategy for the achievement of sustainable development within a circular economy perspective.